Nutrient Content of Pinus merkusi Jungh. et de Vriese Leaf and Its Soil Properties under Varied Resin Production Levels of Stands - Haryono Supriyo; Daryono Prehaten (Jurnal Ilmu Kehutanan)
Economically, the role of pine stands increased because of the value of the resin. The resin has been a flagship product of Perum PERHUTANI. In some areas, resin production varied among compartments. The variation is quite large even the trees were from the same seed origins. This study aimed to study the soil properties and climate, which results in variation of leaf nutrient content. Those were predicted as the cause of differences in the production of resin. The study was conducted in both RPH Ngablak (lower resin production, (<4 g/tree/3 d) and RPH Grabag (higher resin production, (>15 g/tree/3 d), which are located in KPH Kedu Utara. Soil samples were taken in each compartment with three replications. Fresh leaf samples were collected and analyzed for the macro and micro nutrients. The results showed that the pine in Ngablak lies at an elevation of about 1,213 m, while in Grabag it lies on 908 m above sea level. The thickness of the soil’s solum in Ngablak was only 60 cm. The soil was brighter in colors (yellowish red) and many hard stones were found in soil’s profile. Whereas in Grabag the solum was > 90 cm, dark in color (dark brown) and no coarse material in the soil’s profile. Litter biomass, trees height and diameter in Ngablak were only 1,317 tons/ha, 19.3 m and 20.8 cm, respectively. While in Grabag, the litter biomass, trees height and diameter were accounted for 6,857 tons/ha, 31.6 m and 20.8 cm, respectively. The leaf content of Mg and Mn in Ngablak were 0.14 ppm and 86 ppm, respectively, while in Grabag were accounted for 0.27 ppm and 283 ppm, respectively. Nutrient content of C, N, P, K, Ca, Na, Fe, Cu and Zn in both areas were no significant different.